2014
DOI: 10.1038/ncomms6024
|View full text |Cite
|
Sign up to set email alerts
|

Causality-driven slow-down and speed-up of diffusion in non-Markovian temporal networks

Abstract: Recent research has highlighted limitations of studying complex systems with time-varying topologies from the perspective of static, time-aggregated networks. Non-Markovian characteristics resulting from the ordering of interactions in temporal networks were identified as one important mechanism that alters causality and affects dynamical processes. So far, an analytical explanation for this phenomenon and for the significant variations observed across different systems is missing. Here we introduce a methodol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
307
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 300 publications
(327 citation statements)
references
References 50 publications
6
307
0
Order By: Relevance
“…We used the map equation framework, because it was straightforward to generalize its mathematics to second-order Markov dynamics, but the results are, in principle, universal for any method operating on the dynamics on a network 31 . The universality is manifested in the direct effect memory in network flows has on the spectral gap 40,41 . If memory favours spread across a system, the spectral gap increases and, the other way around, if memory confines flow, the spectral gap decreases.…”
Section: Resultsmentioning
confidence: 99%
“…We used the map equation framework, because it was straightforward to generalize its mathematics to second-order Markov dynamics, but the results are, in principle, universal for any method operating on the dynamics on a network 31 . The universality is manifested in the direct effect memory in network flows has on the spectral gap 40,41 . If memory favours spread across a system, the spectral gap increases and, the other way around, if memory confines flow, the spectral gap decreases.…”
Section: Resultsmentioning
confidence: 99%
“…While we do know that real-world diffusion in social or mobility network exhibits non-Markovian patterns [12,26], those patterns sometimes favour, and sometimes reject backtracking regardless of the degree of burstiness of the process, making it clear that they cannot be entirely accounted for by the effect at play in this paper. Whether the burstiness-induced memory is an undesirable artefact of the model or a useful and economical way to generate non-Markovian walks remains to be seen.…”
Section: Discussionmentioning
confidence: 82%
“…Driven by the availability of longitudinal data of empirical networked systems, and the increased importance of temporal networks [7,8], it is only much more recently that researchers have considered how the temporal properties of a network affect diffusion. Empirical observations have shown that temporal properties of networks strongly differ from classical homogeneous Poisson processes, due to their non-stationarity [9], correlations between the activation times of network entities [10][11][12] and fat-tailed inter-event times of activations [13]. A central question is to understand the mechanisms that either accelerate or slow down the diffusion, for instance through the characteristic time for the dynamics to converge to the equilibrium state.…”
Section: Introductionmentioning
confidence: 99%
“…In that respect, it was shown how time ordering interactions, thus causality, affect the interpretation of dynamical processes: in particular, by comparing contrasting features on moderate size time aggregated networks and on their sub-structured time dependent counterparts. Scholtes et al [7], Scholtes et al [8] also showed that some community detection can be made by means of spectral clustering.…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, interesting observations on the diffusion of knowledge in structuring time dependent networks have followed such a path [7,8] . In that respect, it was shown how time ordering interactions, thus causality, affect the interpretation of dynamical processes: in particular, by comparing contrasting features on moderate size time aggregated networks and on their sub-structured time dependent counterparts.…”
Section: Introductionmentioning
confidence: 99%